BUILDING THE ENTREPRENEURSHIP SPIRIT OF STUDENTS THROUGH ENTREPRENEURSHIP TRAINING - Ismuhadi; Azhari; Yusnidar; Ayu Anora; Putri Drissianti (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
The purpose of implementing community service is to learn the theory of entrepreneurship, to learn about entrepreneurial experience, To learn about practices in entrepreneurship. This community service was carried out on October 25-27, 2024, located at Dayah Bustanul Kiram, East Aceh Regency. The service was carried out flexibly, paying attention to and adjusting to conditions in the field (conditions and circumstances). Participants in the implementation of this community service were 15 students of Dayah Bustanul Kiram. From the Entrepreneurship Training activity, it became the first step in building the entrepreneurial spirit of Dayah Bustanul Kiram students. It is hoped that this program will be able to create students who not only have strong religious insight, but are also able to be economically independent through entrepreneurship. Thank you to Dayah Bustanul Kiram, participants, and the implementing team for their support and participation.